ANALISIS BERPIKIR PROBABILISTIK SISWA DALAM MENYELESAIKAN SOAL HOTS DITINJAU DARI GAYA KOGNITIF - Amalia Shofi Kurniawati; Nining Setyaningsih (HISTOGRAM: Jurnal Pendidikan Matematika, 2023)
The probabilistic thinking of junior high school students in Indonesia seems to be still low. It is a concern in education, especially in mathematics learning, solving HOTS  problems in  Algebraic material.   The study aims to analyze students'  probabilistic thinking ability in solving HOTS  questions regarding field-independent and field-dependent cognitive learning styles. The study's methodology consisted of a combination of descriptive techniques and qualitative approaches. Students in the first semester of the 2022-2023 school year at SMP Negeri 1 Polokarto, where the research was conducted, participated in the study. There are a total of four topics, two of which are suited to the Field Independent learning style and two to the Field Dependent method. Students with Field Independent cognitive learning styles were shown to have the requisite level 2 probabilistic thinking capacity, which indicates an ability to communicate. The answer to the question is based on its quantitative ability. Meanwhile,  the achievement of probabilistic thinking ability from students with a  Field Dependent type learning style, namely the ability to think probabilistic at the personal level   (level 1), means that students still require guidance from the teacher so that they can answer the questions appropriately.